Substantial Contraction of Dense Shelf Water in the Ross Sea Under Future Climate Scenarios - Chuan Xie; Zhaoru Zhang; Yuanjie Chen; Chuning Wang (Geophysical Research Letters)
Abstract The Ross Sea in the Southern Ocean is a key region for the Antarctic Bottom Water (AABW) production, primarily originating from the Dense Shelf Water (DSW) formed in polynyas. Here we project future changes in DSW and AABW production in the Ross Sea using a high‐resolution ocean‐sea ice‐ice shelf coupled model that can well capture the observed DSW temporal variability, forced by projected atmospheric perturbations from the CMIP6 multi‐model mean results. Under the high‐emissions scenario, the volume of DSW in the Ross Sea will decrease by ∼26% by 2051–2060 and by ∼51% by 2091–2100 relative to the present, resulting in a reduction of AABW thicknesses by up to 300 m. Such reduction is a combined result of decreased local sea ice production and increased meltwater from the Amundsen Sea ice shelves, which freshens the upper layer of the western Ross Sea and inhibits deep ocean convection.